Effectiveness Test of Learning Devices in the Computer-Aided Manufacturing (CAM) Course - Robert Silaban; Binsar Maruli Tua Pakpahan; Ana Rahmi; Hidir Efendi (Jurnal Penelitian Pendidikan IPA, 2025)
The aim of this research is to develop learning devices, including the syllabus, Semester Learning Plan (RPS), teaching materials, and assessments for the Computer Aided Manufacturing (CAM) course, whose suitability has been tested. The needs analysis is related to the transition from the Competency-Based Curriculum to the Indonesian National Qualifications Framework (KKNI) curriculum, which requires various adjustments. For instance, assessments in the Competency-Based Curriculum consist of four (4) components, while the KKNI curriculum includes six (6) components, with cognitive assessment contributing the most. In its implementation, the Competency-Based Curriculum uses learning devices aligned with its structure. With the adoption of the KKNI curriculum, it is deemed necessary to develop learning devices that support its implementation. This research employs the 4-D model as the basis for the development procedure. The results of the first stage, based on expert evaluations, indicate that the Semester Learning Plan and CAM teaching materials meet the criteria for being highly suitable as learning devices for the CAM course. Additionally, student evaluations confirm that the Semester Learning Plan and CAM teaching materials are appropriate for use as learning devices. The effectiveness test results show a significant increase in post-test scores compared to pre-test scores. Furthermore, the t-test analysis confirms a statistically significant difference between the average post-test and pre-test scores